Surviving COVID-19 and beyond: a conceptual framework for SMEs in crisis - Kahveci, Eyup (Business: Theory and Practice, 2021)
This study sets out to review in detail the available information on SMEs crisis management. Despite SMEs’ crucial role in the economy, relatively little research has been carried out on the effects of the economic crisis on SMEs and how they can cope with a crisis. This work will generate fresh insight into the crisis management for SMEs and provide a clear and easily understandable framework to survive COVID-19 and beyond. Ensuring sound cash flow during the crisis is the center of our framework. It is also crucial to have timely, accurate information and confident, courageous management. It will enable accurate analysis of the situation to restore or establish a new level of homeostasis from the perspective of bounded rationality. There is no generic treatment for overcoming a crisis. Tailor–made strategies and implementations empower companies to approach crisis resolution in the context of equifinality. There is only one goal: to survive the crisis. Yet, every company will have its own unique way to reach this goal.